Impact of EGR and engine speed on HCCI engine performance and tail pipe emissions. (October 2017) - Hassan, A.O.; Abu-jrai, Ahmad; Al-Muhatseb, Ala'a H.; Jamil, Farrukh
Abstract: Increasing air-to-fuel ratio has been considered as one of the advantages of HCCI combustion. A diluted in-cylinder mixture leads to lower temperatures and therefore lower NOx emissions. This improvement is due to a higher trapped residual rate in the cylinder when higher lambda is set. Higher lambda means more air therefore more trapped residual is required to deliver enough energy for auto-ignition. Analysis show that HC, CO in HCCI mode are heavily dependent on engine speed. HC emission was influenced by engine speed more than CO and NOx emissions.